Implementasi Metode SAW Untuk Menentukan Program Bantuan Bedah Rumah Di Kabupaten Pandeglang - Ayu Mira Yunita; Andrianto Heri Wibowo; Robby Rizky; Neli Nailul Wardah (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
The home surgery assistance program is one of the programs of the Department of housing and settlements, where this program is intended to help ease the burden on the poor. Pandeglang regency consists of 35 sub-districts, 13 sub-districts and 326 village with a population of approximately 1,180,000 people with an area of 2,746,89 km2 with a density of 428 people / km, some of whose population work as farmers. Of the many peoply , there are still many resident whosw economic level is very low(poor). The problem in this study is that the housing and settlement office of Pandeglang regency in term of determining the house surgery assistance program is still subjective so that sometime it is not target , as well as the frequent exchange of application document and the lack of transparency of the result of grant recipients. Therefore, a decision support system is needed that ains to make I easier for the housing and settlement office to determine potential recipient of the this method works by finding the weight value for each alternative, then a calculation processs is carried out to obtain an optimal alternative, to determine to potential recipients of the home surgery program. The implementation of the simple additive weighteinig (SAW) methode can provide solutions based on predetermined criteria to determine the priority of potential recipients of home surgical assistance programs, with the highest ranked alternative with a score of 1